Operationalizing One Health: strategic guidance for prevention and control of emerging and re-emerging vector-borne and zoonotic diseases in the Eastern Mediterranean Region - Kodama, Chiori; El Rifay, Amira S.; Badra, Rebecca; Abu Salbi, Rana; Abubakar, Abdinasir; Kayali, Ghazi (Frontiers in Tropical Diseases, 2023)
Operationalizing global One Health strategies at the field level to prevent and control vector-borne and zoonotic diseases (VBZDs) is of significant public health importance. Such strategies should be coordinated at the human–animal–ecosystems interface and applied at the national, regional, and global levels through the enforcement of effective policies. We aimed to develop a regional framework that can aid countries of the World Health Organization Eastern Mediterranean region to better prevent, detect, and respond to VBZDs events. This strategic guidance is a twelve-element framework drafted using various guidance documents and peer-reviewed scientific literatures, incorporating recommendations made through expert consultations. The framework elements were then integrated within a logical framework designed for practical implementation of One Health at regional and country level.